PERLINDUNGAN HUKUM ATAS PEMBERIAN LISENSI DI TANJUNG PINANG FRANCHISE - Monika Melina; Faishal Taufiqurahman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The research is motivated the lack of law protection on giving a license agreement after the enactment regulation No. 42 0f 2007 pertaining of Franchise. The issue of Franchise’s awareness level of its right is quiteweak and it caused an inaccuracy in doing accept all the terms directly. The type is observation research, by surveying or observing straight yo the location with interview as a tool in collecting the data. Whereas, the characteristic of this research descriptive; means that the author tries to give a detail description about implementing legal protection of the giving license agreement after the enactment of government regulation No. 42 of 2007 pertaining to franchise. Based on the result of this research, it can be concluded that implementing of legal protection for franchise hasn’t worked properly. This is evidenced by the amount of franchise rights which is not fulfilled by the franchisor in the agreements that’s franchisee doesn’t even know. This one is because of this one is due to the lack of government’s surveillance and the other authorized party on franchisor rights.